DAMPAK PERUBAHAN USIA PERKAWINAN TERHADAP PERMOHONAN DISPENSASI PERKAWINAN DI PENGADILAN AGAMA TASIKMALAYA - Hamim, Mohamad; Ade Puadah (Ahwaluna | Jurnal Hukum Keluarga Islam, 2024)
The amendment of Law Number 1 of 1974 concerning marriage to Law Number 16 of 2019 concerning the age limit of marriage has caused a high number of marriage dispensations at the Tasikmalaya Religious Court. This change is focused on the age limit for marriage from 16 years old to 19 years old. This study aims to find out the concept of marriage dispensation according to Marriage Law No. 1 of 1974 which was changed to Law No. 16 of 2019, factors that are considered by the Judge in granting the Marriage Dispensation Application at the Tasikmalaya Religious Court and the impact of the enactment of Law No. 16 of 2019. This study uses a qualitative approach that produces descriptive data. The data used were literature studies, documentation and interviews. The result of this study is that the Judge in granting marriage dispensation according to Perma Number 5 of 2019, namely based on the principle of the best interests of the child, the right to life and growth and development of the child, respect for the opinion of the child, respect for human dignity and dignity, non-discrimination, gender equality, equality before the law, justice, usefulness and legal certainty. The amendment to the Marriage Law shows that there was an increase in the number of marriage dispensations submitted to the Tasikmalaya Religious Court in 2018 as many as 31 cases, in 2019 as many as 279 cases, in 2020 as many as 940 cases, in 2021 as many as 1021 cases, in 2022 as many as 775 cases, in 2023 as many as 632 cases, and in 2024 there was a decrease of 222 cases. So the average marriage dispensation at the Tasikmalaya City Religious Court is 571 per year.